2010
DOI: 10.1021/ja910094r
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observations of Oxygen-induced Platinum Nanoparticle Ripening Studied by In Situ TEM

Abstract: This study addresses the sintering mechanism of Pt nanoparticles dispersed on a planar, amorphous Al(2)O(3) support as a model system for a catalyst for automotive exhaust abatement. By means of in situ transmission electron microscopy (TEM), the model catalyst was monitored during the exposure to 10 mbar air at 650 degrees C. Time-resolved image series unequivocally reveal that the sintering of Pt nanoparticles was mediated by an Ostwald ripening process. A statistical analysis of an ensemble of Pt nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
388
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 391 publications
(411 citation statements)
references
References 62 publications
18
388
5
Order By: Relevance
“…For instance, one could anticipate that ''Pt-skin'' nanoparticles should exhibit improved activity over Pt in comparison to ''Pt-skeleton'' nanoparticles. However, surface impurities, surface segregation of the solute metal, 160 sintering, 166 and degradation of the carbon support 167 all complicate the annealing process on nanoparticles. Nonetheless, several research groups have reported the synthesis of ''Pt-skin'' structures upon carbon-supported Pt-alloy nanoparticles.…”
Section: Strategies To Improve the Performance Of Pt-alloy Nanoparticlesmentioning
confidence: 99%
“…For instance, one could anticipate that ''Pt-skin'' nanoparticles should exhibit improved activity over Pt in comparison to ''Pt-skeleton'' nanoparticles. However, surface impurities, surface segregation of the solute metal, 160 sintering, 166 and degradation of the carbon support 167 all complicate the annealing process on nanoparticles. Nonetheless, several research groups have reported the synthesis of ''Pt-skin'' structures upon carbon-supported Pt-alloy nanoparticles.…”
Section: Strategies To Improve the Performance Of Pt-alloy Nanoparticlesmentioning
confidence: 99%
“…This highlights the importance of the in situ study on the sintering kinetics, as well documented in the literature. 26,46,47,74 Journal of the American Chemical Society 2.4. Reactant Induced Disintegration.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…As discussed above, environmental studies can be performed in an ETEM with the use of conventional sample holders (Hansen et al, 2001;Helveg et al, 2004;Kim et al, 2010;Simonsen et al, 2010) or in a traditional TEM by use of a dedicated sample holder with a high pressure cell (Creemer et al, 2008). In both cases the setup defines the boundary conditions regarding gas, pressure and temperature.…”
Section: The Value Of Complementary Experiments -Bridging Gapsmentioning
confidence: 99%